2001
DOI: 10.1093/ndt/16.12.2365
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of immature forearm fistulas for haemodialysis by interventional radiology

Abstract: Delayed maturation of native fistulas should lead systematically to imaging as an underlying stenosis is diagnosed in all cases. Interventional radiology can treat the majority of cases and achieve a 97% success rate but early recurrence of stenoses can occur. Multidisciplinary re-evaluation of the patient must, therefore, be performed after radiological salvage of the fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
156
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(169 citation statements)
references
References 20 publications
8
156
0
5
Order By: Relevance
“…In other words, the majority (over two thirds) of new AVFs matured, despite sonographic evidence for postoperative stenosis and no prophylactic intervention to repair the stenosis. Previous reports have observed a high frequency of juxta-anastomotic or draining vein stenosis in immature AVFs, with angioplasty converting many of them to mature AVFs (17,18). Taken together, these findings suggest that stenosis is necessary but not sufficient for the pathogenesis of AVF nonmaturation.…”
Section: Discussionmentioning
confidence: 58%
“…In other words, the majority (over two thirds) of new AVFs matured, despite sonographic evidence for postoperative stenosis and no prophylactic intervention to repair the stenosis. Previous reports have observed a high frequency of juxta-anastomotic or draining vein stenosis in immature AVFs, with angioplasty converting many of them to mature AVFs (17,18). Taken together, these findings suggest that stenosis is necessary but not sufficient for the pathogenesis of AVF nonmaturation.…”
Section: Discussionmentioning
confidence: 58%
“…However, we strongly believe that endovascular treatment should be attempted before surgery is considered for the following reasons: (1) We and others (22)(23)(24)33) have demonstrated that endovascular treatment is associated with excellent success rates, low complication rates, and promising long-term patency rates (24). Most important, this is done without the introduction and assistance of synthetic polytetrafluroethylene grafts.…”
Section: Discussionmentioning
confidence: 99%
“…In another analysis, Turmel-Rodrigues et al (11) demonstrated the successful application of endovascular techniques to salvage an AVF that had failed to mature.…”
Section: Interventions To Salvage With Early Avf Failurementioning
confidence: 99%